On the Appearance of Elastoplastic Pulses Generated by Pulsed Beams of Charged Particles on the Back Surface of a Metallic Target - Boiko [i. e. Boyko] B. I. Vladimir Ilyich (2001, 2001)
The results of the numerical simulation of the appearance of mechanical pulses caused by the impact action of pulsed beams of charged particles onto the free back surface of a metallic target are given. The numerical experiments are based on the model of pulsed loading of an elastohydrodynamic medium. The dynamics of the parameters of state near the back surface of the target are studied. The mechanisms that deter-mine the processes on the back surface of a metallic target under the action of a high-power pulsed ion and a high-current electron beam are established. It is shown that the action of an electron beam leads to the genera-tion of a large number of modifying factors that cause structural changes at the back surface of the metallic tar-get, whereas the action of an ion beam is not accompanied by any destructive changes.